Study of aerobic bacteriology profile of chronic suppurative otitis media - Ujwala A Lokhande,; Suresh L Akulwar,; Annasaheb Lokhande, (Asian Journal of Medical Sciences, 2024)
Background: Chronic suppurative otitis media (CSOM) poses a recurring and persistent challenge in otolaryngology, stemming from diverse etiologies. Understanding the regional prevalence of the predominant etiological agent and its antimicrobial susceptibility is crucial for effective management. Aims and Objectives: This study aims to determine the aerobic bacterial profile and prevalent bacterial etiology responsible for CSOM in our geographical setting. Materials and Methods: Conducted over 2 years in the microbiology department of a tertiary care hospital, this study enrolled 504 clinically diagnosed otitis media cases. Participants, presenting with discharging ears at the E.N.T. department, met inclusion criteria of chronic otitis media with or without complications. Patients had not received treatment for at least 7 days before sample collection. Results: Among the 402 CSOM samples, aerobes were isolated from 70.15%, anaerobes from 73.63%, and mixed isolates (aerobes+anaerobes) from 38.06%. Solely aerobes were present in 32.08% of samples, while solely anaerobes were found in 35.57%. Monomicrobials constituted 75.88%, and polymicrobials accounted for 24.11% of the samples. Conclusion: In conclusion, this study enhances our understanding of CSOM microbiology in our region, providing insights into organism prevalence, mixed infections, and antibiotic sensitivity. The findings offer clinicians valuable data for tailored treatment strategies, emphasizing the need for individualized scrutiny to address the dynamic nature of CSOM bacteriology over time.